An Important Tool in Lymphedema Management: Validation of the Turkish Version of the Gynecologic Cancer Lymphedema Questionnaire - Abakay , Hanife; Abdulrezzak, Ummuhan; Akbayrak, Turkan (Gynecology Obstetrics & Reproductive Medicine, 2023)
OBJECTIVE: This study aimed to research the reliability and validity of the Turkish version of the gynecologic cancer lymphedema questionnaire for individuals with gynecologic cancer. STUDY DESIGN: The study included 60 patients who underwent gynecologic cancer surgery with lower limb lymphedema in the lymphedema group and 30 who underwent gynecologic cancer surgery without lower limb lymphedema in the non-lymphedema group. The Turkish adaptation of the gynecologic cancer lymphedema questionnaire was completed by considering the cultural adaptation process. For the evaluation of lymphedema, circumference measurement, skin layer thickness, and lymphoscintigraphy assessments were performed. The intraclass correlation coefficient was calculated for gynecologic cancer lymphedema questionnaire test-retest reliability, the Cronbach alpha was calculated for internal consistency reliability and the criteria validity method was used for survey validity. RESULTS: The symptom subsections and total score of the gynecologic cancer lymphedema questionnaire, the intraclass correlation values for test-retest points were 0.780, 0.968, 0.695, 0.945, 0.896, 0.945, and 0.947. The Cronbach a values for internal consistency were 0.928, 0.824, 0.656, 0.429, 0.923 and 0.948 for the subsections. Criteria validity was used for the validity analysis and statistically significant (p<0.05) positive correlations were determined between skin fold thickness measurements and total points on the scale in the lymphedema group for values at the midpoint of the right and left tibial shaft (r=0.336, r=0.284). CONCLUSION: The gynecologic cancer lymphedema questionnaire was determined to be a reliable and valid scale to differentiate patients with lower limb lymphedema from those without lower limb lymphedema in a Turkish female population.